The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1016/s2213-2600(21)00125-9
|View full text |Cite
|
Sign up to set email alerts
|

Confronting COVID-19-associated cough and the post-COVID syndrome: role of viral neurotropism, neuroinflammation, and neuroimmune responses

Abstract: Cough is one of the most common presenting symptoms of COVID-19, along with fever and loss of taste and smell. Cough can persist for weeks or months after SARS-CoV-2 infection, often accompanied by chronic fatigue, cognitive impairment, dyspnoea, or pain—a collection of long-term effects referred to as the post-COVID syndrome or long COVID. We hypothesise that the pathways of neurotropism, neuroinflammation, and neuroimmunomodulation through the vagal sensory nerves, which are implicated in SARS-CoV-2 infectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
218
0
14

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 251 publications
(239 citation statements)
references
References 95 publications
7
218
0
14
Order By: Relevance
“…Of foremost importance, for COVID-19 patients having been discharged to home, is diarying daily oxygen saturation levels, pulse rate, and body temperature. Specific details regarding consultation with a physician include oxygen saturation levels declining below 93%; 22 - 26 pulse rate >100 heart beats per min; 27 - 29 fever above 100.4° Fahrenheit (38° Celsius) or excessive chilling with or without tremor (rigors); 30 - 33 difficulty breathing with >24 respirations per min; 27 , 30 , 34 - 36 shortness of breath 30 ; worsening cough with our without productive sputum 30 , 37 - 39 ; development of nausea, vomiting or diarrhea or worsening of any of these signs 33 , 40 - 42 ; new onset chest pain or chest pressure that does not resolve; confusion 43 - 45 ; sleep disorder 46 ; evidence of cyanotic or erythematous skin discoloration of the oral labia or face or the skin of the toes or fingers 33 , 47 - 52 ; a generalized feeling of worsening 53 - 62 which may necessitate prompt remeasuring and dairying of the oxygen saturation level.…”
Section: Resultsmentioning
confidence: 99%
“…Of foremost importance, for COVID-19 patients having been discharged to home, is diarying daily oxygen saturation levels, pulse rate, and body temperature. Specific details regarding consultation with a physician include oxygen saturation levels declining below 93%; 22 - 26 pulse rate >100 heart beats per min; 27 - 29 fever above 100.4° Fahrenheit (38° Celsius) or excessive chilling with or without tremor (rigors); 30 - 33 difficulty breathing with >24 respirations per min; 27 , 30 , 34 - 36 shortness of breath 30 ; worsening cough with our without productive sputum 30 , 37 - 39 ; development of nausea, vomiting or diarrhea or worsening of any of these signs 33 , 40 - 42 ; new onset chest pain or chest pressure that does not resolve; confusion 43 - 45 ; sleep disorder 46 ; evidence of cyanotic or erythematous skin discoloration of the oral labia or face or the skin of the toes or fingers 33 , 47 - 52 ; a generalized feeling of worsening 53 - 62 which may necessitate prompt remeasuring and dairying of the oxygen saturation level.…”
Section: Resultsmentioning
confidence: 99%
“…In fact, the prevalence of long-term post-COVID-19 cough almost one year after COVID-19 could be considered smaller than expected [ 7 ]. Previous meta-analyses reported a pooled prevalence of post-COVID-19 cough ranging from 14 to 18% at follow-ups shorter than 3 months after infection [ 6 , 8 , 9 ]. The prevalence of long-term post-COVID-19 cough was smaller (2.5%), suggesting that maybe post-COVID-19 cough naturally decreases during the first year after SARS-CoV-2 infection.…”
Section: Discussionmentioning
confidence: 99%
“…Another meta-analysis focusing on respiratory post-COVID-19 symptoms found a pooled prevalence of post-COVID-19 cough of 14% (95%CI 6–24%, n = 8 studies) [ 8 ]. Similarly, Song et al also reported a prevalence of 18% (95%CI 12–24%, n = 14 studies) for post-COVID-19 cough in previously hospitalized survivors [ 9 ]. All studies included in these meta-analyses had follow-up periods ranging from 3 to 12 weeks [ 6 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Antimuscarinic drugs, such as tiotropium, could be used to control COVID-19 cough, because these can decrease cough sensitivity in cases of acute viral upper respiratory tract infection. 9 The importance of multidisciplinary rehabilitation has been acknowledged for patient management post-COVID.…”
mentioning
confidence: 99%